A thermodynamic analysis and economic evaluation of an integrated lignite upgrading and power generation system. (5th May 2018) - Xu, Cheng; Sun, Yang; Xin, Tuantuan; Xu, Gang; Zhu, Mingming; Yang, Yongping; Zhang, Dongke
Highlights: The proposed system efficiently produces exportable upgraded coal and electricity. Energy efficiency of the proposed highly-integrated system reaches 79.6%. Equivalent energy conversion ratio for lignite upgrading soars to 100.8%. Produced upgraded coal is more economical for energy transmission in China. Abstract: Effective upgrading for efficient utilisation of lignite is of great significance for countries that highly dependent on coal for power generation. This work proposed and evaluated an integrated system for lignite upgrading and utilisation using pre-drying, low-temperature oxidative pyrolysis (LTOP) and power generation, beneficially converting lignite into an exportable thermal coal while generating power locally. In the proposed system, LTOP was adopted to upgrade lignite, and the pre-drying process would reduce the moisture content of lignite prior to LTOP and boiler using steam bleeds from the conjunct steam turbine, saving a part of reaction heat consumed by moisture evaporation. The energy of raw syngas produced in LTOP process was efficiently utilised by co-combusting with a portion of pre-dried lignite in boiler, and the sensible heat of upgraded coal was recovered by preheating the feed/condensate water of steam turbine unit. With the developed models and process simulation, the mass and energy balance of the proposed integrated system for upgrading Zhundong lignite (ZD) in conjunction with a 600 MW supercritical electric power plant were determined. Detailed thermodynamic analysis showed that the proposed system produces annually 1.66 million tonnes of exportable upgraded coal with lower heating value (LHV) of 29.45 MJ/kg, as well as 3118.5 GWh electricity, with overall energy efficiency at 79.6% and the ratio of produced electricity over the energy of upgrade coal product at 22.9%. As a considerable technical route for long-distance energy transportation, economics of deploying the proposed systems in north-western China and exporting the upgraded coal (TR-I) to the eastern seaboard over a distance of 3000 km was quantified, and compared with the option of adopting ultra-high voltage (UHV) electric power transmission (TR-II). It was shown that, the overall CAPEX of TR-I is ∼59% less than that of TR-II and the gross cost of electricity (COE) of TR-I is ₵5.20/kWh, also much lower than that of the TR-II.